Cyberbullying perpetration and victimisation among junior and senior high school students in Guangzhou, China. Issue 1 (6th April 2017) - Rao, Jiaming; Wang, Haiqing; Pang, Minhui; Yang, Jianwei; Zhang, Jiayi; Ye, Yunfeng; Chen, Xiongfei; Wang, Shengyong; Dong, Xiaomei
Abstract : Objectives: Cyberbullying research in China is in early stage. This study describes the cyberbullying experiences of junior and senior high school students in Guangzhou, China, and to examine the risk factors associated with cyberbullying perpetrators, victims and perpetrator-victims among students. We also investigated the frequency of cyberbullying and coping strategies of student victims. Methods: Participants were 2590 students in grades 7, 8, 9 and 10 from six junior and senior high schools in October 2015 in Guangzhou, in south China, who completed a questionnaire. Data on participants' experiences with cyberbullying perpetration and victimisation during the previous 6 months were collected. Multinomial logistic regression was used to analyse factors associated with being perpetrators, victims and perpetrator-victims. Results: In this sample, 28.0% (725) of participants reported being a perpetrator and 44.5% (1150) reported being a victim in the previous 6 months. Specifically, 2.9% (74) reported being perpetrators only, 19.3% (499) reported being victims only and 25.2% (651) reported being perpetrator-victims (both perpetrator and victim). In addition, flaming was the most common form of cyberbullying in both perpetration and victimisation. Logistic regression analyses indicated that online game addiction in participants was associated with increased odds of being a perpetrator only; no democratic parenting style in the mother and physical discipline by parents were associated with increased odds of being a victim only; male students, students with low academic achievement, those spending over 2 hours a day online, experiencing physical discipline from parents and online game addiction were associated with increased odds of both perpetration and victimisation. Conclusions: Cyberbullying is a common experience among Chinese junior and senior high school students. These findings add to the empirical data on cyberbullying and reinforce the urgent need for cyberbullying prevention in China. Furthermore, from the perspective of practice, it is important to raise our awareness of cyerbullying and reduce the risk factors.